A review of non‐glove personal protective equipment‐related occupational dermatoses reported to EPIDERM between 1993 and 2013. (10th January 2019) - Bhoyrul, Bevin; Lecamwasam, Kamalini; Wilkinson, Mark; Latheef, Faheem; Stocks, Susan J.; Agius, Raymond; Carder, Melanie
Abstract : Background: Personal protective equipment (PPE) is defined as equipment that protects the wearer's body against health/safety risks at work. Gloves cause many dermatoses. Non‐glove PPE constitutes a wide array of garments. Dermatoses resulting from these have hitherto not been documented. Objectives: To determine the incidence and types of non‐glove PPE‐related dermatoses. Patients/Methods: We analysed incident case reports from dermatologists of non‐glove PPE‐related dermatoses to a UK‐wide surveillance scheme (EPIDERM) between 1993 and 2013. Results: The dermatoses associated with non‐glove PPE accounted for 0.84% of all occupational skin disease. Of all PPE‐related cases, 194 (9.2%) were attributable to non‐glove PPE. Of these, 132 (68.0%) occurred in men, and the median age (both male and female) was 42 years (range 18‐82 years). The non‐glove PPE‐related dermatoses were diagnosed as: allergic contact dermatitis (47.4%), irritant contact dermatitis (16.0%), friction (11.3%), occlusion (11.3%), unspecified dermatitis (8.8%), acne (3.1%), infections (1.5), and contact urticaria (0.52%). The industries most associated with non‐glove PPE‐related dermatoses were manufacturing (18.6%), public administration and defence (17.0%), health and social work (15.5%), and transport, storage, and communication (9.8%). Conclusions: Clothing, footwear, facemasks and headgear need to be recognized as causes of dermatoses occurring at body sites less commonly associated with occupational skin disease.